PEMBERIAN PUPUK UREA DAN PUPUK KANDANG KAMBING PADA TANAH ULTISOL BILAH HULU PADA PERTUMBUHAN PRODUKSI TANAMAN PAKCOY (Brassica rapa L) - Fitra Syawal Harahap; Mulya Rafika; Zuriani Ritonga; Rendi Fitra Yana (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
Application of Urea Fertilizer and Goat manure in a Ultisol for green mustard plants (Brassica Chinensis L.) aimed to determine the fertilizer treatment of goats sometimes goats to increase leaf area, root volume, and fresh weight of plants. And Interaction of fertilizer application, sometimes goat fertilizer (ts/ha) and urea fertilizer on green mustard plants. This research was conducted in Sona Village with a height of 18 meters above sea level in Labuhanbatu Regency in December 2019 until March 2020. The material used was green mustard seeds, goat manure. Urea fertilizer, water Tools used are cutter blades, analytical scales, rulers, scissors, mortars, measuring flasks, buckets, calipers, neat ropes, hoes. The research will be conducted with a factorial group design. The first factor is the provision of factorial Group Design consisting of 2 factors, the first factor is Goat Cage fertilizer (K) consisting of 3 levels and the second factor is the provision of Urea fertilizer consisting of 2 dose levels, so we get 6 treatment combinations every 4 replications so that 24 plots were obtained. Each plot consisted of 25 plants and taken 5 plants as samples. The parameters observed were plant height (cm), number of leaves (strands), leaf area (cm2), root volume (ml), and weight of fresh plant weight (g). Data obtained from the results of the study were statistically analyzed with variance and continued with Duncan's New Multiple Range Test (DNMRT) at a 5% level. Results of research The treatment of fertilizer sometimes goat (ts/ ha) with a dose of 2 ts/ha and urea fertilizer at 100 kg/ha can increase leaf area, root volume, and plant fresh weight. As well as the interaction of fertilizer application, sometimes goat fertilizer (t / ha) and urea fertilizer have a significant influence on the parameters of leaf area, root volume, and plant fresh weight.